Differentiation of periapical granuloma from radicular cyst using cone beam computed tomography images texture analysis. Issue 10 (October 2020) - De Rosa, Catharina Simioni; Bergamini, Mariana Lobo; Palmieri, Michelle; Sarmento, Dmitry José de Santana; de Carvalho, Marcia Oliveira; Ricardo, Ana Lúcia Franco; Hasseus, Bengt; Jonasson, Peter; Braz-Silva, Paulo Henrique; Ferreira Costa, Andre Luiz
Abstract: Objective: This study aimed to investigate the use of texture analysis for characterization of radicular cysts and periapical granulomas and to assess its efficacy to differentiate between both lesions with histological diagnosis. Methods: Cone beam computed tomography (CBCT) images were obtained from 19 patients with 25 periapical lesions (14 radicular cysts and 11 periapical granulomas) confirmed by biopsy. Regions of interest were created in the lesions from which 11 texture parameters were calculated. Spearman's correlation analysis was performed and adjusted with Benjamini-Hochberg false discovery rate procedure (FDR <0.005). Results: The texture parameters used to differentiate the lesions were assessed by using a receiver operating characteristic analysis. Five texture parameters were predictive of lesion differentiation for eight positions: angular second moment; sum of squares; sum of average; contrast; correlation. Conclusion: Texture analysis of CBCT scans distinguishes radicular cysts from periapical granulomas and can be a promising diagnostic tool for periapical lesions. Clinical significance: Texture analysis can be used in diagnostic and treatment monitoring to provide supplementary information. Abstract : Pathology; Dentistry; Oral Medicine; Eye-Ear-Nose-Throat; Radiology; Medical Imaging; l cone beam computed tomography; computer-assisted diagnosis; image processing, computer-assisted; periapical diseases.